KINERJA LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN DAN KOTA DI SUMATERA UTARA BERDASARKAN OPINI AUDIT - Panggabean, Fitri Yani (Universitas Medan Area, 2019)
The aims of the study is to explore the results of the audit opinion given by Badan Pemeriksa Keuangan on the local government financial statement in North Sumatra by using financial documents for the 2014 fiscal year. This research is a descriptive study which reveals the results of the auditor's opinion on the local government financial statement. The research population is the object of local government in the province of North Sumatra in 2014 fiscal year. The research sample consisted of 33 local government financial statement documents in North Sumatra. The type of data used is secondary data. Based on the audit report conducted by the auditors from the audit findings of the local government financial statement in Nort Sumatra, the results such as the auditor?s opinion reasonable without any exception as many as 13 local government; the auditor?s opinion is unqualified with an explanatory paragraph consisting of two local governments; the auditor?s opinion is reasonable with the exception consisting of 15 local governments; the auditor?s opinion doen not provide an opinion consisting of three local govenrment. The findings obtained that the dominance of auditor opinion is reasonable with the exception, and there are three local governments with opinions not giving opinions. Consistenly with these findings, the regional government in North Sumatra must be able to improve and commit to transparency in the use of regional finances, so that the auditor's opinion in the future is better and more beneficial to the community.